The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1002/jor.21101
|View full text |Cite
|
Sign up to set email alerts
|

Correlating femoral shape with patellar kinematics in patients with patellofemoral pain

Abstract: Summary The etiology of patellofemoral pain is likely related to pathological femoral shape and soft-tissue restraints imbalance. These factors may result in various maltracking patterns in patients with patellofemoral pain. Thus, we hypothesized that femoral shape influences patellofemoral kinematics, but that this influence differs between kinematically-unique subgroups of patients with patellofemoral pain. 3D MRIs of 30 knees with patellofemoral pain and maltracking (“maltrackers”) and 33 knees of asymptoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
91
3
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(100 citation statements)
references
References 39 publications
4
91
3
2
Order By: Relevance
“…There is an association between trochlear dysplasia and patellar maltracking. Differences were found in femoral shape between maltracking and asymptomatic cohorts in a recent patellofemoral kinematics study [19]. It was also shown that trochlear dysplasia is an important contributing factor to patellofemoral instability [20].…”
Section: Discussionmentioning
confidence: 95%
“…There is an association between trochlear dysplasia and patellar maltracking. Differences were found in femoral shape between maltracking and asymptomatic cohorts in a recent patellofemoral kinematics study [19]. It was also shown that trochlear dysplasia is an important contributing factor to patellofemoral instability [20].…”
Section: Discussionmentioning
confidence: 95%
“…Innocenti et al (2011) carried out a design-of-experiments (DOE) style analysis (varying patella alta/baja position and internal-external (I-E) rotation, as well as tibial parameters) in four different implanted geometries, determining that PF contact forces were primarily affected by patellar height. Several studies have investigated correlations between PF kinematics and patellar or femoral shape measures in the natural knee (Harbaugh et al, 2010;Sheehan et al, 2009;Jafari et al, 2008;Powers, 2000). Heinert et al (2011) and implanted knees in a cadaveric study, attributing kinematic differences to sulcus groove geometry.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that there is a mismatch between the bony and cartilaginous anatomy of the trochlea (Staubli et al 1999;Shih et al 2004) but possible influence on patellar instability was not evaluated. Harbaugh et al (2010) and Teng et al (2014) reported that the lateral trochlear inclination (LTI) was more important in predicting patellar lateral displacement, than sulcus angle.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that females with PFP might have greater medial femoral rotation when compared to the pain free individuals. different opinions exist regarding morphometric characteristics of the patellofemoral joint and their influence on patellar alignment and PFP (Powers 2000;Harbaugh et al 2010;Varadarajan et al 2010). The purpose of this study was to use full weight bearing kinematic MRI, to systematically examine relationships among patellofemoral malalignment; morphologic features of the trochlea groove, femoral and patellar rotation and to determine which measures are the best predictors for PFP.…”
Section: Introductionmentioning
confidence: 99%